1993
DOI: 10.1002/ijc.2910530425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular heterogeneity of wilms' tumor

Abstract: We developed a Wilms' tumor-cell culture system to investigate the molecular basis of nephrogenesis and oncogenesis. Several distinct fractions of cells were isolated and characterized from the same tumor specimen. The cells exhibited striking differences in morphology, immunocytochemical staining profiles and cytogenetics. One fraction contained cells with features of epithelium; other cell fractions resembled partially differentiated mesenchyme (blastema or stroma). While the Wilms' tumor-suppressor gene WT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(6 reference statements)
0
6
0
2
Order By: Relevance
“…In order to determine if chromosome 12 duplications or amplifications are involved in cyclin D2 and/or CDK4 overexpression, we are currently studying 60 tumors for chromosome 12 abnormalities. Previous studies, looking for RB LOH in WT, indicated the lack of involvement of this tumor suppressor gene in WT [45,46]. However, if the increased level of cyclin D2 and CDK4 message produces more of their protein complexes, then RB-mediated G1-phase arrest may be inhibited.…”
Section: Discussionmentioning
confidence: 94%
“…In order to determine if chromosome 12 duplications or amplifications are involved in cyclin D2 and/or CDK4 overexpression, we are currently studying 60 tumors for chromosome 12 abnormalities. Previous studies, looking for RB LOH in WT, indicated the lack of involvement of this tumor suppressor gene in WT [45,46]. However, if the increased level of cyclin D2 and CDK4 message produces more of their protein complexes, then RB-mediated G1-phase arrest may be inhibited.…”
Section: Discussionmentioning
confidence: 94%
“…The most widely investigated is the WTI gene, which is mapped to Ip 13. The p53 gene has also been suggested to play a role in the pathogenesis of nephroblastomas (Lemoine et al, 1992;Velasco et al, 1993). This study looked at the prognostic significance of the immunohistochemical detection of p53 protein in nephroblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Wilms' tumour suppressor gene (WT1), mapped within chromosome 11p13 18,19 , is the best known anti-oncogene associated with Wilms' tumour, p53 mutations 11,13 have occasionally been implicated in the pathogenesis of Wilms' tumour. The concept of multiple sites of genetic 'hits', besides 11p13, seems feasible in the evolution of Wilms' tumour as cytogenetic studies have identified aberrations within 11p15 and 16q in some cases 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of p53 alterations in paediatric tumours is however less well established. Conflicting reports regarding the possible existence of p53 mutations in Wilms' tumour (nephroblastoma) have emerged from various studies [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%